Clinical Performances and Biological Features of Clear Aligners Materials in Orthodontics - Macrì, Monica; Murmura, Giovanna; Varvara, Giuseppe; Traini, Tonino; Festa, Felice (Frontiers in Materials, 2022)
In recent years, aesthetic concerns regarding orthodontic appliances have significantly increased due to the increasing growing number of adult patients undergoing orthodontic therapy. Clear removable aligners have seen growing popularity as an aesthetic and comfortable alternative to traditional fixed appliances. Clear aligner therapy also appears more respectful of the patient's periodontal health; in fact, clear aligners allow the patients to maintain proper daily oral hygiene thanks to being removable. Among the parameters that affect the clinical efficacy of aligners, the material employed for their manufacturing plays a key role. The present paper aims to review the most used materials in manufacturing clear aligners, focusing on their clinical and mechanical performances, according to the current state of literature. Furthermore, biological features of the different materials are also examined regarding their effects on dental and periodontal tissues, oral mucosa, and potential systemic effects.